2010
DOI: 10.3382/ps.2009-00308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic inclusion levels in broiler nutrition on growth performance, nutrient digestibility, plasma immunoglobulins, and cecal microflora composition

Abstract: The aim of this work was to investigate the effect of inclusion levels of a 5-bacterial species probiotic in broiler nutrition. Five hundred twenty-five 1-d-old male Cobb broilers were allocated in 5 experimental treatments for 6 wk. The experimental treatments received a corn-soybean coccidiostat-free basal diet and depending on the addition were labeled as follows: no addition (C), 10(8) cfu probiotic/kg of diet (P1), 10(9) cfu probiotic/kg of diet (P2), 10(10) cfu probiotic/kg of diet (P3), and 2.5 mg of av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
248
5
38

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(315 citation statements)
references
References 31 publications
24
248
5
38
Order By: Relevance
“…The enhanced colonization of the intestines with the microflora, apart from significant effects on the host's growth performance, gut immunity and development, can increase the energy requirements for the maintenance of the bacterial population inhabiting the chickens' gastrointestinal tract. It was also demonstrated by Mountzouris et al (2010) that the inclusion of the growing dosages of probiotics into broilers' feed caused the proportional increase in the FCR, especially in the grower and finisher growth phases. It is generally accepted that the bacterial species inhabiting the gut compete for the nutrients with the host, which results in an higher energy uptake (Furuse and Yokota, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced colonization of the intestines with the microflora, apart from significant effects on the host's growth performance, gut immunity and development, can increase the energy requirements for the maintenance of the bacterial population inhabiting the chickens' gastrointestinal tract. It was also demonstrated by Mountzouris et al (2010) that the inclusion of the growing dosages of probiotics into broilers' feed caused the proportional increase in the FCR, especially in the grower and finisher growth phases. It is generally accepted that the bacterial species inhabiting the gut compete for the nutrients with the host, which results in an higher energy uptake (Furuse and Yokota, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary treatments were (1) CON (antibiotic free diet), (2) ANT1 (CON + enramycin 5 ppm), (3) ANT2 (CON + avilamycin 5 ppm), (4) TSP1 (CON + 0.1% TSP), and (5) TSP2 (CON + 0.2% TSP). It is well accepted that enramycin and avilamycin can be used as antibiotic growth promoters (AGPs) to compare the efficacy of probiotics (Mountzouris et al 2010;Abudabos 2012). Broiler chickens were raised in a temperature-controlled room with three floors of stainless steel pens of identical size (1.75 × 1.55 m).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the poultry industry must develop alternatives to antibiotics to maintain health and performance under commercial conditions. Probiotics have been increasingly adopted as an alternative to antibiotic growth promoters in poultry diets (Mountzouris et al 2010;Zhang and Kim 2014). Probiotics, which are live cultures of harmless bacteria or yeast species that equilibrate intestinal microflora to benefit the host (Ferencik et al 2000;Chen et al 2013), have been demonstrated to be helpful in maintaining the intestinal ecosystem and enhancing animal health.…”
mentioning
confidence: 99%
“…Probiotic bacteria have numerous and different influences on the host. The use of probiotics which can help to improve poultry performance (Bai et al, 2013;Amerah et al, 2013;Apata, 2008;Mountzouris et al, 2007) improves intestinal microbial balance (Fuller, 1989;Mountzouris et al, 2010) and immune response (Talebi et al, 2008;Apata, 2008). Naglaa (2013) studied the effects of probiotics on turkey behaviour.…”
Section: Introductionmentioning
confidence: 99%